Peran Kelompok Sosial Keagamaan dalam Melakukan Transformasi Sosial di Masa Pandemi Covid-19 di Kalimantan Timur - Syobah, Sy. Nurul; Kusuma, Rudy Hadi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The mergence of COVID-19 in 2019–2022 has impacted social change in Indonesian society. The need to implement health protocols to prevent COVID-19 also has an impact on religious activities. For that reason, religious organisations such as Nahdlatul Ulama (NU) and Muhammadiyah, which are agents of social change, play an active role in tackling this phenomenon. This research employs a qualitative, phenomenological approach. The Nahdlatul Ulama Branch Manager (PCNU) and the Muhammadiyah District Manager (PDM) of Balikpapan City, Paser District, and East Kutai District, along with religious figures, public figures, and communities in the three locations, serve as the primary data sources in this study. Gathering techniques through interviews. Data analysis techniques consist of data condensation, data display, and conclusion drawing or verification. The research results revealed that the Nahdlatul Ulama Branch Manager (PCNU) and the Muhammadiyah District Manager (PDM) in the Eastern Kalimantan district continued to conduct limited face-to-face religious social activities while also increasing their use of Zoom and social media. In addition, the social programmes carried out by the PCNU and the PDM collaborated with the government and MUI, including vaccination programmes, socio-economic assistance, and the development of health protocols in even cross-religious communities.